2020
DOI: 10.3390/agronomy10040601
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Transverse Distribution of Fertilizer in Coffee Plantations

Abstract: Considering the impact of fertilizers on coffee production costs, the search for greater efficiency in the use of these inputs has an important role. Accordingly, the aim of the present study is to evaluate the transverse distribution of fertilizer by a centrifugal spreader in a coffee plantation and to compare two operating modes: fertilizer application on one side (FA1), or both sides (FA2) of the coffee plants. In addition, three doses (200, 300 and 400 kg ha−1) of monoammonium phosphate and three spreading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
2
0
2
Order By: Relevance
“…In many cases, it is an all-in-one system, including GNSS receiver and monitor, while it is sometimes a more complex system consisting of a GNSS receiver, monitor, actuator, controller for spatially variable rate crop input application, etc. [19][20][21][22]. A low-cost solution available online for building up a homemade automatic guidance system is offered by AgOpenGPS project, which provides the outlines and designs of the hardware to be developed, as well as the software that is distributed together with GNU (General Public) license.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, it is an all-in-one system, including GNSS receiver and monitor, while it is sometimes a more complex system consisting of a GNSS receiver, monitor, actuator, controller for spatially variable rate crop input application, etc. [19][20][21][22]. A low-cost solution available online for building up a homemade automatic guidance system is offered by AgOpenGPS project, which provides the outlines and designs of the hardware to be developed, as well as the software that is distributed together with GNU (General Public) license.…”
Section: Introductionmentioning
confidence: 99%
“…The insertion of efficient precision coffee techniques in coffee crops can be found in many studies. When evaluating the transversal application of variable rate fertilizers, Andrade et al [13] defined optimal lateral fertilizer distribution, and created an efficient and practical method for this type of analysis. Mapping plant attributes in a coffee crop, Ferraz et al [14], demonstrated the importance of this mapping category for coffee crop management.…”
Section: Introductionmentioning
confidence: 99%
“…As configurações dos discos (KHUDHER; HIMOUD; ALMALIKI, 2020a; KIM; WOO; KIM, 2018;SAGRILO et al, 2019;YANG et al, 2019;YILDIRIM;KARA, 2012), posicionamento (PRZYWARA et al, 2020;RAMON, 2003a) e abertura da alimentação de fertilizantes sobre o disco (COETZEE; LOMBARD, 2011;SHI et al, 2018). Também foram avaliados a velocidade de giro dos discos que interfere na balística de projeção das partículas e consequentemente no padrão de distribuição do insumo (ANDRADE et al, 2020;DINTWA et al, 2004;GANASCINI et al, 2016;OLIESLAGERS;DE BAERDEMAEKER, 1996), os tipos de dosadores (SPAGNOLO et al, 2021), as características dos fertilizantes utilizados (PETTERSEN;SVENDSEN;ØVLAND, 1991;YULE, 2011) O distribuidor pneumático é caracterizado por conter um sistema de turbina ou ventilador que produz fluxo e pressão de ar suficiente para a condução do insumo do reservatório até as pontas de aplicação (HIGGINS, 2003;SRIVASTAVA et al, 2006).…”
Section: Mecanismos Distribuidoresunclassified
“…Nos poucos trabalhos existentes (ABBOU- OU-CHERIF et al, 2017;SPAGNOLO et al, 2021) 2016). Nestes equipamentos, diversos fatores que afetam a qualidade da aplicação tem sido intensamente estudados (ANDRADE et al, 2020;KHUDHER;HIMOUD;ALMALIKI, 2020;KIM;WOO;KIM, 2018;LAGHARI et al, 2014;SAGRILO et al, 2019;SPAGNOLO et al, 2021;WERNER et al, 2007), porém, a aplicação de produtos em pó é um assunto que carece de mais estudos, já que a aplicação de corretivos de acidez do solo ou fertilizantes em pó, não é uma prática comum em todos os países.…”
Section: Introductionunclassified